Disseminated Cryptococcosis in Man: Decreased Lymphocyte Transformation in Response to Cryptococcus neoformans - Diamond, Richard D.; Bennett, John E. (The Journal of infectious diseases, 1973)
Heat-killed Cryptococcus neoformans, a yeast-like fungus, was used to stimulate in-vitro incorporation of thymidine by human lymphocytes. Lymphocytes from control subjects previously exposed to cryptococci (positive skin tests) had significantly higher uptake of thymidine than cells from unexposed control subjects (negative skin tests). Uptake by lymphocytes from successfully treated patients with cryptococcosis was low when compared with that of exposed control subjects. It is suggested that defective function of lymphocytes may reflect increased susceptibility to cryptococcal infection in some patients with cryptococcosis without any other known predisposing factors.